Front Antagonism Towards Social and Political Integration Perspectives on the Social Science of Prophetic - Pababbari, Musafir (Jurnal Adabiyah, 2020)
This research is talking about conflict antagonism which is a social phenomenon that often confuses sociologists. It is not an interesting problem, but because of the same phenomenon discussed, but the results are always the opposite. Especially in seeing the nature of conflicts that occur in society. Conflict is usually dysfunctional in society but at the same time becomes structural. This study uses the conflict method proposed by Lewis Coser to discuss societies that have a pattern of social integration of processes that address structural conflicts so that dynamic societies seek a form of balance. The results showed that the conflict that occurred to achieve the intended purpose was social support. Social legitimacy formed by press groups will produce horizontal conflicts and vice versa if it is legally agreed by consensus then it will become an integration tool. So far, many ideas have been resolved in conflict resolution for integration purposes. This research is reviewed from the perspective of prophetic social science, one of the important ideas of Kuntowijoyo. For him, social science should not be complacent in trying to explain or understand reality, but social science must also carry the task of transformation towards ideals that are idealized by society. Three basic values as the basis of prophetic social science, namely: humanization, liberation, and transcendence.يتحدث هذا البحث عن عداوة الصراع وهي ظاهرة اجتماعية غالبًا ما تربك علماء الاجتماع. ليس بسبب مشكلة مثيرة للاهتمام، ولكن بسبب نفس الظاهرة التي نوقشت، لكن النتائج دائمًا ما تكون عكس ذلك. خاصة في رؤية طبيعة الصراعات التي تحدث في المجتمع .عادة ما يكون الصراع غير فعال في المجتمع ولكن في نفس الوقت يصبح هيكلية .تستخدم هذه الدراسة طريقة الصراع التي اقترحها لويس كوسر لمناقشة المجتمعات التي لديها نمط من التكامل الاجتماعي للعمليات التي تعالج الصراعات الهيكلية، بحيث تسعى المجتمعات الديناميكية إلى شكل من أشكال التوازن .أظهرت النتائج أن الصراع الذي حدث لتحقيق الغرض المقصود كان الدعم الاجتماعي .ستؤدي الشرعية الاجتماعية التي تشكلها المجموعات الصحفية إلى صراع أفقي والعكس صحيح إذا تمت الموافقة عليها قانونًا بتوافق الآراء، فسوف تصبح أداة تكام . حتى الآن، تم حل العديد من الأفكار في حل النزاعات لأغراض التكامل. تتم مراجعة هذا البحث من منظور العلوم الاجتماعية النبوية، وهي واحدة من أفكار Kuntowijoyo الهامة .بالنسبة له، لا ينبغي أن يكون العلم الاجتماعي مقتصرا في محاولة تفسير الواقع أو فهمه، ولكن يجب أن يحمل العلم الاجتماعي أيضًا مهمة التحول نحو المثل العليا التي يعتبرها المجتمع مثالية. هناك ثلاث قيم أساسية كأساس لعلم الاجتماع النبوي، وهي الإنسانية والتحرير والتعالي.Penelitian ini berbicara tentang antagonisme konflik yang merupakan fenomena sosial yang sering membingungkan sosiolog. Bukan karena masalah yang menarik, tetapi karena fenomena yang sama yang dibahas, tetapi hasilnya selalu berlawanan. Terutama dalam melihat sifat-sifat konflik yang terjadi di masyarakat. Konflik biasanya disfungsional dalam masyarakat tetapi pada saat yang sama menjadi struktural. Penelitian ini menggunakan metode konflik yang diusulkan oleh Lewis Coser untuk membahas masyarakat yang memiliki pola integrasi sosial dari proses yang mengatasi konflik struktural, sehingga masyarakat yang dinamis mencari bentuk keseimbangan. Hasil penelitian menunjukkan bahwa konflik yang terjadi untuk mencapai tujuan yang dimaksud adalah dukungan sosial. Legitimasi sosial yang dibentuk oleh kelompok pers akan menghasilkan konflik horizontal dan sebaliknya jika disetujui secara sah melalui konsensus maka itu akan menjadi alat integrasi. Sejauh ini, banyak ide telah diselesaikan dalam resolusi konflik untuk tujuan integrasi. Penelitian ini diulas dari perspektif Ilmu sosial profetik, salah satu ide penting dari Kuntowijoyo. Baginya, ilmu sosial tidak boleh berpuas diri dalam mencoba menjelaskan atau memahami realitas, tetapi ilmu sosial juga harus membawa tugas transformasi menuju cita-cita yang diidealkan oleh masyarakat. Tiga nilai dasar sebagai dasar ilmu sosial profetik, yaitu: humanisasi, pembebasan, dan transendensi.